PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP MOTIVASI BELAJAR PAK SISWA KELAS VIII SMP N.1 SIPAHUTAR T.P 2019/2020. - Samuel Hamonangan Simanjuntak (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
This research aims to determine the influence of the Model of Quantum Learning on the students’ motivation to learn Christian Religion Education of grade VIII in SMP Negeri 1 Sipahutar 2019/2020. Research hypothesis is: there is the influence of the Model of Quantum Learning on the students’ motivation to learn Christian Religion Education of grade VIII in SMP Negeri 1 Sipahutar 2019/2020.This research is a correlational study that uses an inferential quantitative method. The population is Christian students of grade VIII in SMP Negeri 1 Sipahutar numbering 256 people. Samples were taken 20% of 256 people = 51 people. The research instrument is a closed poll.Results of analysis shows that r2 = 0,605 0, 297and Tcount = 5.320 2.021 indicating that there is an influence of the Model of Quantum Learning on the students’ motivation to learn Christian Religion Education of grade VIII in SMP Negeri 1 Sipahutar 2019/2020. The hypothesis test obtained fcount = 20,753 1.51 then H0 is rejected and Ha is accepted. This research concludes that there is an influence of the Model of Quantum Learning on the students’ motivation to learn Christian Religion Education of grade VIII in SMP Negeri 1 Sipahutar 2019/2020. Keywords: The Model of Quantum Learning, students’ motivation to learn Christian Religion Education.